Treatment of amiodarone-induced thyrotoxicosis resistant to conventional therapy - Nišić Tanja (Medicinski Glasnik Specijalne Bolnice za Bolesti Štitaste Žlezde i Bolesti Metabolizma "Zlatibor", 2017)
Introduction: Amiodarone as an antiarrhythmic medication is necessary in the prevention and treatment of malignant ventricular arrhythmias, however, it can induce thyroid dysfunction. Thyroid dysfunction may be either hypothyroidism or thyrotoxicosis, however, 50% of patients who have used amiodarone are euthyroid. Case report: A 27-year-old female patient, hospitalized at the Clinic for Endocrinology due to type 2 amiodarone-induced thyrotoxicosis. The patient had previously received amiodarone for two years. At age 25, the patient was diagnosed with dilated cardiomyopathy (EF 25%, EDD/ESD 56-57/47 mm) with mild Ebstein’s anomaly, WPW Sy and recorded episodes of non-sustained VT. In order to reduce the risk of sudden death and prevent malignant ventricular arrhythmias, ICD-VR was implanted and amiodarone was prescribed. Treatment with propylthiouracil (PTU) and dexamethasone was initiated after thyrotoxicosis was diagnosed. Three weeks after the introduction of PTU, hepatotoxicity was registered, thus the medication was discontinued. Thyrozol, which regulates the hepatotoxicity parameters, was introduced. Sodium perchlorate and glucocorticoid (per os, IV and intrathyroidal) therapy was introduced. The treatment had lasted for fifty days and laboratory signs of thyrotoxicosis were still present, which is why a total of eight plasmapheresis sessions were performed. Each plasmapheresis resulted in a significant decrease in FT4 and a slight decrease in FT3. After seventy two days of treatment, an optimal hormonal status of the thyroid gland was established and total thyroidectomy was performed. Conclusion: Patient was treated for amiodarone-induced thyrotoxicosis (AIT) type 2, which was resistant to conventional therapy for a long period of time. Successful treatment was achieved by applying plasmapheresis although the effect of perchlorate and glucocorticoids application cannot be disregarded.